Faktor – Faktor Perilaku Konsumen Yang Mempengaruhi Keputusan Jumlah Pembelian Tahu Di Pabrik Tahu KLB Jalan Pelabuhan Ketapang 1 Kelurahan Bakalan Krajan, Kecamatan Sukun, Kota Malang - Canggul, Adrianus; Triwulan Budisaptorini, Anasthasia; Perwita Rahmanti Ignatia, Sari (BiSTeK Pertanian, 2024)
. Tofu is a soybean product which is very popular and widely produced in Indonesia. Tofu is white in color and has a soft and creamy texture. This study aims to analyze buying-motivation factor, reference group, consumer income, and the place of buying influence the decision on the number of tofu-buying at the KLB Tofu Factory and to determine the dominant factors influencing the decision to buy tofu. This research was conducted at the KLB Tofu Factory, Jalan Pelabuhan Ketapang 1, Kelurahan Bakalan Krajan, Kecamatan Sukun, Malang City. The study’s sampling method is sampling accidental. The study’s population is 525 people and the sample is 84 respondents using the Slovin formula with an error rate of 10%. Data were collected using questionnaires from 84 respondents who were samples from tofu consumers who bought tofu directly at the KLB Tofu Factory. The analytical tool used in this study is the multiple linear regression analysis using the f test (simultaneous), t test (partial); and the dominant factor influencing the decision on the number of tofu buying at the KLB Tofu Factory is determined by comparing the beta value (ꞵ) or the magnitude of the beta coefficient (ꞵ) on the results of the t test (partial). The results show that simultaneously the independent variable (X) has a significant effect on the dependent variable (Y) the number of tofu buying. Variables that partially have a significant effect are buying motivation, reference group, and consumer income. While the place of purchase variable has no significant effect on the number of tofu buying. The dominant factor that influences the number of tofu purchases is buying motivation. The value of the beta coefficient (ꞵ) of buying motivation is greater than the value of the reference group, consumer income, and place of purchase.